Maternal Socialization of Child Emotion and Adolescent Adjustment: Indirect Effects through Emotion Regulation - Perry, Nicole B. (Dev Psychol, 2020)
A fundamental question in developmental science is how parental emotion socialization processes are associated with children’s subsequent adaptation. Few extant studies have examined this question across multiple developmental periods and levels of analysis. Here, we tested whether mothers’ supportive and non-supportive reactions to their 5-year-old children’s negative emotions were associated with teacher- and adolescent self-reported adjustment at age 15 via children’s physiological and behavioral emotion regulation at age 10 (N=404). Results showed that maternal supportive reactions to their children’s negative emotions were associated with children’s greater emotion regulation in a laboratory task and also a composite of mother- and teacher reports of emotion regulation at age 10. Maternal non-supportive reactions to their children’s negative emotions were uncorrelated with supportive reactions, but were associated with poorer child physiological regulation and also poorer mother- and teacher-reported emotion regulation at age 10. In turn, better physiological regulation at age 10 was associated with more adolescent-reported social competence at age 15. Furthermore, teacher- and mother-reports of emotion regulation at age 10 were associated with increased adolescent adjustment across all domains. Mediational effects from non-supportive and supportive reactions to adolescent adjustment tested via bootstrapping were significant. Our findings suggest that mothers’ reactions to their children’s negative emotions in early childhood may play a role in their children’s ability to regulate their arousal both physiologically and behaviorally in middle childhood, which in turn, may play a role in their ability to manage their emotions and behaviors and to navigate increasingly complex social contexts in adolescence.